A review of friction stir welding of aluminium matrix composites - Salih, Omar S.; Ou, Hengan; Sun, W.; McCartney, D.G. (Elsevier, 2015)
As a solid state joining process, friction stir welding (FSW) has proven to be a promising approach for joining aluminium matrix composites (AMCs). However, challenges still remain in using FSW to join AMCs even with considerable progress having been made in recent years. This review paper provides an overview of the state of-the-art of FSW of AMC materials. Specific attention and critical assessment have been given to: (a) the macrostructure and microstructure of AMC joints, (b) the evaluation of mechanical properties of joints, and (c) the wear of FSW tools due to the presence of reinforcement materials in aluminium matrices. This review concludes with recommendations for future research directions.